KEPUASAAN KONSUMEN TERHADAP BAURAN PEMASARAN DI USAHA â€œWARONG KOBONGâ€ MANADO (Consumer Satisfaction to Marketing Mix in Manado Warong Kobong Business) - Glory Amelia Sekeon; Joachim N. K. Dumais; Paulus A. Pangemanan (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2020)
The objective of this research is to determine consumer power over the marketing mix in the Manado Warong Kobong business . This research was conducted in May until July 2019. This research used primary data by means of cousiner to 80 respondents or consumers to fill in then cousiner sheets were collected, processed and then analyzed the return of samples using the accidental sampling method that is the researcher chose who the members the population accidentally meets with researchers thought to be able to provide information that can be needed. The research result showed that consumer satisfaction with the marketing mix in Manado Warong Kobong business is satisfied related to the four variables namely production, price, place and promotion.Keywords: Consumer Satisfaction, Manado Warong Kobong Business